2018
DOI: 10.1002/jum.14834
|View full text |Cite
|
Sign up to set email alerts
|

How Many Cores Does Systematic Prostate Biopsy Need?: A Large‐Sample Retrospective Analysis

Abstract: Objectives To explore the best individualized systematic prostate biopsy method. Methods We retrospectively analyzed the clinical data of 1211 patients who underwent 12‐core systematic prostate biopsy guided by transrectal ultrasound from January 2011 to March 2018. Other biopsy core methods (6‐, 8‐, and 10‐core) were estimated from the 12‐core biopsy that was performed. Differences in the detection rates of prostate cancer (PCa) and clinically significant prostate cancer (csPCa) were compared. Results A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Several studies found that the PI-RADS score was a significant independent predictor of csPCa at biopsy (24,25). In studies such as that of Hu et al (16), this type of research did not include mpMRI data and only included tumor-related factors, and found that for patients with a PSA concentration of 20 ng/ml or higher, a 6-core systematic biopsy is preferred. However, we obtained fewer biopsy cores (5 cores and 4 cores) under stricter statistical conditions; therefore, we included the mpMRI data, especially the PI-RADS score, which is an important factor for core reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found that the PI-RADS score was a significant independent predictor of csPCa at biopsy (24,25). In studies such as that of Hu et al (16), this type of research did not include mpMRI data and only included tumor-related factors, and found that for patients with a PSA concentration of 20 ng/ml or higher, a 6-core systematic biopsy is preferred. However, we obtained fewer biopsy cores (5 cores and 4 cores) under stricter statistical conditions; therefore, we included the mpMRI data, especially the PI-RADS score, which is an important factor for core reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the existence of many unstable factors in MRI-guided prostate biopsy, an alternative approach is to reduce the number of cores on systemic biopsy. Current research has focused on specific factors, such as prostate volume or PSA level, to reduce the cores of systematic biopsy ( 16 ), or analyzed different hypothetical sampling schemes when compared with targeted biopsy plus 12-SBx ( 17 ). Fewer studies have reported the reduction of cores after individualization of patients according to the location of suspicious lesions on MRI, and a variety of factors are not yet sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with another recently published study comparing different biopsy protocols. Hu et al [21] demonstrated that a 10- or 12-core biopsy scheme revealed higher detection rates than 6- or 8-core biopsy methods. However, in contrast to our study, Hu et al [21] did not include patients with a prebiopsy MRI.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Hu et al [21] demonstrated that a 10- or 12-core biopsy scheme revealed higher detection rates than 6- or 8-core biopsy methods. However, in contrast to our study, Hu et al [21] did not include patients with a prebiopsy MRI. In 2018, Oishi et al [18] investigated men with a prebiopsy negative MRI followed by a 12-core SB.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Results showed that the sextant method detected 9% more PCa 3 , 22 , 24 , 41 and ensuing research regarding systematic schemes supported the modern standard of a 10–14 core regimen with additional targeted biopsies to maintain diagnostic accuracy while minimizing complication risk. 42 , 43 Although the first TR PBx efforts using finger-guided approach were described in 1937 by Astraldi et al 4 and involved a finger-guided approach, it was not until these landmark publications by Hodge et al providing evidence for TR PBx efficacy and convenience that allowed for it to become the standard for PBx 40 and for TP biopsies to fall nearly obsolete.…”
Section: Early Efforts To Transperineally Biopsy the Prostatementioning
confidence: 99%